SARS‐CoV‐2 sculpts the immune system to induce sustained virus‐specific naïve‐like and memory B‐cell responses. Issue 9 (5th September 2021) - de Campos‐Mata, Leire; Tejedor Vaquero, Sonia; Tachó‐Piñot, Roser; Piñero, Janet; Grasset, Emilie K; Arrieta Aldea, Itziar; Rodrigo Melero, Natalia; Carolis, Carlo; Horcajada, Juan P; Cerutti, Andrea; Villar‐García, Judit; Magri, Giuliana
Abstract: Objectives: SARS‐CoV‐2 infection induces virus‐reactive memory B cells expressing unmutated antibodies, which hints at their emergence from naïve B cells. Yet, the dynamics of virus‐specific naïve B cells and their impact on immunity and immunopathology remain unclear. Methods: We longitudinally profiled SARS‐CoV‐2‐specific B‐cell responses in 25 moderate‐to‐severe COVID‐19 patients by high‐dimensional flow cytometry and isotyping and subtyping ELISA. We also explored the relationship of B‐cell responses to SARS‐CoV‐2 with the activation of effector and regulatory cells from the innate or adaptive immune system. Results: We found a virus‐specific antibody response with a broad spectrum of classes and subclasses during acute infection, which evolved into an IgG1‐dominated response during convalescence. Acute infection was associated with increased mature B‐cell progenitors in the circulation and the unexpected expansion of virus‐targeting naïve‐like B cells. The latter further augmented during convalescence together with virus‐specific memory B cells. In addition to a transitory increase in tissue‐homing CXCR3 + plasmablasts and extrafollicular memory B cells, most COVID‐19 patients showed persistent activation of CD4 + and CD8 + T cells along with transient or long‐lasting changes of key innate immune cells. Remarkably, virus‐specific antibodies and the frequency of naïve B cells were among the major variables defining distinct immune signatures associated with disease severity and inflammation. Conclusion: Aside from providing new insights into the complexity of the immune response to SARS‐CoV‐2, our findings indicate that the de novo recruitment of mature B‐cell precursors into the periphery may be central to the induction of antiviral immunity. Abstract : We longitudinally studied moderate‐to‐severe COVID‐19 patients to dissect SARS‐CoV‐2‐specific B cell responses overtime. We found a broad virus‐specific antibody response during acute infection, which evolved into an IgG1‐dominated response. Moreover, we identified a persistent expansion of virus‐targeting naïve‐like and memory B cells in COVID‐19 patients, as well as unique immune signatures that associated with disease severity and inflammation.